Struggling with capital: a Bourdieusian analysis of educational strategies among internationally mobile middle class families in Sweden. Issue 5 (3rd September 2019) - Waddling, Jennifer; Bertilsson, Emil; Palme, Mikael
ABSTRACT: Drawing on empirical data regarding educational strategies among internationally mobile families in the Stockholm-Uppsala region, this study questions the notion of a global middle class. First, a quantitative analysis shows that immigrating middle class professionals and their children are few, having marginal impact on the demand for international education. Furthermore, they far from constitute a homogeneous class, instead comprising of fractions opting for different types of schools. A second, qualitative study on capital conversion among mobile families illustrates that even well-educated international movers face serious challenges converting their existing knowledge, skills and contacts into well-informed social, professional and educational strategies in their new context. This suggests the limitations of concepts such as international capital. It is argued that the GMC concept overshadows the fact that social groups within the middle classes have varying degrees of international mobility that constitutes just one dimension of what separates them from each other.